2019
DOI: 10.1186/s13046-019-1437-z
|View full text |Cite
|
Sign up to set email alerts
|

CircWHSC1 promotes ovarian cancer progression by regulating MUC1 and hTERT through sponging miR-145 and miR-1182

Abstract: BackgroundCircular RNAs are key regulators in human cancers, however, there is a lack of studies on circRNAs’ specific functions in ovarian cancer.MethodsOur study used qRT-PCR to detect the differentially expressed circRNAs between normal ovaries and ovarian cancer tissues. Cell function experiments were performed to verify the role of overexpression and silence of circWHSC1, including MTT assay, cell apoptosis assay, wound healing and Matrigel-coated Transwell assay. In vivo tumorigenesis model was construct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
87
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(90 citation statements)
references
References 38 publications
2
87
0
1
Order By: Relevance
“…31 And circWHSC1 was showed to accelerate the progression of OC through the regulation of MUC1 and hTERT by directly targeting miR-145 and miR-1182. 32 Coincident with these findings, our outcomes indicated that circ_0025033 was abnormally overexpressed in OC tissues and cells. Moreover, knockdown of circ_0025033 brought about the repression of cell viability, migration, invasion and EMT process but the motivation of apoptosis in OC cells, giving the potent explanation for the pro-tumor role of circ_0025033 in OC evolution.…”
Section: Discussionsupporting
confidence: 76%
“…31 And circWHSC1 was showed to accelerate the progression of OC through the regulation of MUC1 and hTERT by directly targeting miR-145 and miR-1182. 32 Coincident with these findings, our outcomes indicated that circ_0025033 was abnormally overexpressed in OC tissues and cells. Moreover, knockdown of circ_0025033 brought about the repression of cell viability, migration, invasion and EMT process but the motivation of apoptosis in OC cells, giving the potent explanation for the pro-tumor role of circ_0025033 in OC evolution.…”
Section: Discussionsupporting
confidence: 76%
“…In many cancer types, miR-1182 has been considered to be a tumor suppressor regulating cancer progression, such as colorectal cancer, ovarian cancer, and prostate cancer. [20][21][22] Recent studies by Li et al have shown that miR-1182 can be absorbed by circ_0000735 and then participates in the regulation of circ_0000735 on NSCLC. 23 Therefore, miR-1182 mainly plays an anticancer role in NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…This circRNA was confirmed to function as an oncogenic circRNA and may represent a novel promising biomarker and therapeutic strategy for OvCa. Zong et al found that circWHSC1 was highly expressed in OvCa and was able to adsorb miR-145 and miR-1182 to upregulate the expression of downstream targets Mucin 1 (MUC1) and human telomerase reverse transcriptase (hTERT) [64]. MUC1 is a highly expressed gene in a variety of cancers, including OvCa, and is known to participate in tumorigenicity, initiate the EMT process, and coordinate cancer metastasis [65][66][67].…”
Section: Hsa_circ_0001387mentioning
confidence: 99%